Anxiety and Depressive Symptoms among Ischaemic Heart Disease Patients in a Malaysian Tertiary University Hospital - Suzaily Wahab,; Shamsul Azhar Shah,; Soo, Tze Hui; Siti Juliana Hussin,; Mohd Fekri Ahmat Nazri,; Izzatul Izzanis Abd Hamid,; Rosdinom Razali,; Tuti Iryani Daud,; Syahnaz Mohd Hashim,; Umi Kalthum,; Abdul Hamid Abdul Rahman, (Universiti Kebangsaan Malaysia, 2015)
Introduction: Anxiety and depression were known to bring detrimental outcome in patients with ischemic heart disease (IHD). Notwithstanding their high prevalence and catastrophic impact, anxiety and depression were unrecognized and untreated. The aim of this study was to determine the prevalence of anxiety and depression among IHD patients and the association of this condition with clinical and selected demographic factors. Methods: This was a cross-sectional study on 100 IHD patients admitted to medical ward in UKMMC. Patients diagnosed to have IHD were randomly assessed using Hospital Anxiety and Depression Scale (HADS) and Perceived Social Support (PSS) Questionnaire. Socio-demographic data were obtained by direct interview. Fifteen percent of IHD patients in this sample were noted to have anxiety, fourteen percent noted to have depression while thirty two percent was noted to have both anxiety and depression. Patients’ age group and the duration of illness were found to have significant association with anxiety. Socio-demographic data were obtained by direct interview. Results: Fifteen percent of IHD patients in this sample were noted to have anxiety, fourteen percent noted to have depression while thirty two percent was noted to have both anxiety and depression. Patients’ age group and the duration of illness were found to have significant association with anxiety. The other clinical and selected demographic factors such as gender, race, marital status, education level, occupation, co-existing medical illness and social support were not found to be significantly associated with anxiety or depression among the IHD patients. Conclusions: In conclusion, proper assessment of anxiety and depression in IHD patients, with special attention to patients’ age and duration of illness should be carried out routinely to help avert detrimental consequences.